МУЗИЧНИЙ ТВІР ЯК ПРЕДМЕТ ЕСТЕТИЧНОГО АНАЛІЗУ В ПРАЦЯХ Р. ІНГАРДЕНА (Педагогіка вищої та середньої школи, 2022)
In this article the analysis of musical work its peculiarities of performance and perception in R. Ingard’s monography (polish philosopher) is considered.